2018
DOI: 10.1002/anie.201804729
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Direct Olefination of Methyl‐Substituted Heteroarenes with Primary Alcohols

Abstract: Herein, we present the first catalytic direct olefination of methyl-substituted heteroarenes with primary alcohols through an acceptorless dehydrogenative coupling. The reaction is catalyzed by a complex of the earth-abundant transition metal manganese that is stabilized by a bench-stable NNN pincer ligand derived from 2-hydrazinylpyridine. The reaction is environmentally benign, producing only hydrogen and water as byproducts. A large number of E-disubstituted olefins were selectively obtained with high effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 91 publications
1
43
2
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][60][61][62][63] Metal-ligand cooperative catalysis [64][65][66][67] can dramatically improve catalytic performance of ADC reactions using pincer ligands bearing NH, OH or CH 2 functionality. [40][41][42][43][44][68][69][70][71][72][73][74][75][76][77][78][79][80][81] Milstein, [40] Sun, [41] Yu, [42] Kundu [43] and Chen [44] have independently developed bifunctional Ru(II) catalysts for the synthesis of pyridine and quinoline derivatives (Scheme 1), but these catalysts were often air/water sensitive, involved a somewhat complicated synthesis, or required to...…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][60][61][62][63] Metal-ligand cooperative catalysis [64][65][66][67] can dramatically improve catalytic performance of ADC reactions using pincer ligands bearing NH, OH or CH 2 functionality. [40][41][42][43][44][68][69][70][71][72][73][74][75][76][77][78][79][80][81] Milstein, [40] Sun, [41] Yu, [42] Kundu [43] and Chen [44] have independently developed bifunctional Ru(II) catalysts for the synthesis of pyridine and quinoline derivatives (Scheme 1), but these catalysts were often air/water sensitive, involved a somewhat complicated synthesis, or required to...…”
Section: Introductionmentioning
confidence: 99%
“…While Kempe and co‐workers approached the reaction with the PNP−Mn complex Mn‐22 (Scheme a), Maji et al. used an in situ generated NNN‐pincer stabilized complex Mn‐23 for the ADC of N ‐heteroarenes 12 with 1 (Scheme b) . In both cases, it was found that the reaction was highly selective and gave only Z‐isomer of the olefination product 13 .…”
Section: C−c Bond Formationmentioning
confidence: 99%
“…Diverse reactions of hydrogenation, dehydrogenation and others have been successfully achieved . Recently, Maji and coworkers described a manganese pincer complex catalyzed olefination reaction of methyl‐substituted heteroarenes with primary alcohols (Scheme ) . An NNN pincer ligand derived from 2‐hydrazinylpyridine was shown to be essential to this transformation.…”
Section: Olefination Reactions With Alcoholsmentioning
confidence: 99%
“…[30] Recently, Maji and coworkers described a manganese pincer complex catalyzed olefination reaction of methyl-substituted heteroarenes with primary alcohols (Scheme 11). [31] An NNN pincer ligand derived from 2-hydrazinylpyridine was shown to be essential to this transformation. A variety of disubstituted olefins were synthesized with exclusive E-configuration, which find extensive applications in pharmaceuticals, agrochemicals and synthetic intermediates.…”
Section: Olefination Reactions With Alcoholsmentioning
confidence: 99%